2022
DOI: 10.1021/jacsau.1c00529
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and Specificity Details of Mucin 1 O-Glycosylation Process by Multiple Polypeptide GalNAc-Transferase Isoforms Unveiled by NMR and Molecular Modeling

Abstract: The large family of polypeptide GalNAc-transferases (GalNAc-Ts) controls with precision how GalNAc O-glycans are added in the tandem repeat regions of mucins (e.g., MUC1). However, the structural features behind the creation of well-defined and clustered patterns of O-glycans in mucins are poorly understood. In this context, herein, we disclose the full process of MUC1 O-glycosylation by GalNAc-T2/T3/T4 isoforms by NMR spectroscopy assisted by molecular modeling protocols. By using MUC1, with four tandem repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Note that the MUC1 TR contains two bis- O -glycosites and one isolated glycosite. We previously showed that all five O -glycosites are fully O -glycosylated when expressed in glycoengineered HEK293 cells and that BT4244 efficiently cleaves the Tn glycoform of this MUC1 reporter with predominant cleavage in between the bis- O -glycan at the VTSA and GSTA motifs 24 , 37 . We tested the wt glycoform of the MUC1 TR reporter (containing a mixture of mono and disialylated core 1 and core 2 structures), and three engineered more homogeneous glycoforms with mSTa, T, and Tn O -glycans.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Note that the MUC1 TR contains two bis- O -glycosites and one isolated glycosite. We previously showed that all five O -glycosites are fully O -glycosylated when expressed in glycoengineered HEK293 cells and that BT4244 efficiently cleaves the Tn glycoform of this MUC1 reporter with predominant cleavage in between the bis- O -glycan at the VTSA and GSTA motifs 24 , 37 . We tested the wt glycoform of the MUC1 TR reporter (containing a mixture of mono and disialylated core 1 and core 2 structures), and three engineered more homogeneous glycoforms with mSTa, T, and Tn O -glycans.…”
Section: Resultsmentioning
confidence: 95%
“…This suggests that AM0627 and BT4244 should behave very similarly in terms of recognition towards bis- O -glycan and that BT4244 likely cleaves glycopeptides containing bis- O -glycans. In fact, it has been recently shown that BT4244 acts on glycopeptides with bis- O -glycans, in particular G S*T* A and V T*S* A motifs of the Tn-MUC1-TR reporter, while it is inactive in a single PD T* R O -glycosite 24 , 37 (S* or T* denotes a GalNAc-glycosylated Ser and Thr, respectively). With respect to the other mucinases, while ZmpB and ZmpC do not have an aromatic residue close to the sugars at the G subunits, IMPa contains two threonines (Thr775 and Tyr776) that will likely clash with both the GalNAc and Gal at the G1 and G2 subunits, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-translational modification of proteins by glycans may take place by multiply O-glycosidically linked N -acetyl- d -galactosamine residues or by larger complex oligosaccharides . Chemical shift displacements upon glycosylation of peptides and proteins, monitored by, e.g., 1 H, 15 N-HSQC or 1 H, 1 H-TOCSY NMR experiments, can be utilized as specific identifiers on sites of modification and the process of sequential addition of glycans to the polypeptide chain. The importance of glycosylation in biochemical systems will in future studies be further unraveled by the detailed analysis of the interplay between glycans and polypeptides, where NMR spectroscopy will play an essential role.…”
Section: Discussionmentioning
confidence: 99%
“…Here, DWCTVs could expose tumor antigenic Gal/GalNAc epitopes and reduce sialic acids, conferring them with immunostimulatory potential. The 1-hydroxyl of GalNAc is attached to the hydroxyl group of the protein serine (Ser) or threonine (Thr) residues for initiation of glycosylation by N -acetylgalactosaminyltransferase (ppGalNAc-T) [ 46 ], and 3- and 6-hydroxyls of GalNAc could be linked with sialic acids to terminate glycosylation by α-2,3-sialyltransferase (ST3GAL ΙΙ) and α-2,6-sialyltransferase (ST6GAL I) [ 47 ]. Tn (GalNAcα1-O-Ser/Thr), T (Galβ1-3GalNAcα1-O-Ser/Thr), and STn (NeuAcα2-6GalNAcα1-O-Ser/Thr) antigens are widely expressed in several types of tumors [ 48 ].…”
Section: Discussionmentioning
confidence: 99%